If a4+b4=a2 then find a6+b6
Answers
Answered by
32
Hi there,
I think your question has some missing elements in it because the provided information is not giving any proper solution. Hoping the proper question to be as follows:
If a4+b4=a2b2 then find a6+b6
Step-by-step explanation:
It is given that,
a⁴ + b⁴ = a²b²
rearranging this equation
⇒ a⁴ + b⁴ – a²b² = 0 …… (i)
Now, let’s solve for
a⁶ + b⁶
= (a²)³ + (b²)³
= (a² + b²)[(a²)² - a²b² + (b²)²] …… [using algebraic formula: a³ + b³ = (a+b)(a²-ab+b²)]
= (a² + b²)[a⁴ - a²b² + b⁴]
= (a² + b²) * 0 ……. [substituting from (i)]
= 0
Thus, a⁶ + b⁶ = 0
Answered by
0
Answer:
answer is 0 (a²+b²)*0 =0
the above texted answer is correct .
Similar questions
English,
7 months ago
Environmental Sciences,
7 months ago
Environmental Sciences,
1 year ago
Physics,
1 year ago